The effect of reinforcement volume ratio on porosity and thermal conductivity in Al-Mgo composites - Recep Calin; Muharrem Pul; Zühtü Onur Pehlivanli (Materials Research, 2012)
In this study, the effects of reinforcement volume ratios (RVR) on composite structure and thermal conductivity were examined in Al-MgO reinforced metal matrix composites (MMCs) of 5%, 10% and 15% RVR produced by melt stirring. In the production of composites, EN AW 1050A aluminum alloy was used as the matrix material and MgO powders with particle size of -105 µm were used as the reinforcement material. For every composite specimen was produced at 500 rev/min stirring speed, at 750 °C liquid matrix temperature and 4 minutes stirring time. Composite samples were cooled under normal atmosphere. Then, microstructures of the samples were determined and evaluated by using Scanning Electron Microscope (SEM) and Energy Dispersive X-ray Spectroscopy (EDS) analysis. In general, it was observed that the reinforcement exhibited a homogeneous distribution. Furthermore, it was determined that the increase in the RVR increased porosity. From the Scanning Electron Microscope images, a thermal Ansys model was generated to determine effective thermal conductivity. Effective thermal conductivity of Al-MgO composites increased with the decrease in reinforcement volume ratio.